2022
DOI: 10.1155/2022/7122276
|View full text |Cite|
|
Sign up to set email alerts
|

Application Research and Case Analysis of Landscape Design in Artificial Intelligence Platform

Abstract: Modern landscape greening plays an important role in the construction of modern cities and plays a positive role in improving the natural environment of cities and building a good image of cities. With the continuous progress of society and technology, human’s understanding of artificial intelligence is deepening, and intelligent technology is gradually integrated into all aspects of life. Because media technology has rich design elements and can carry out rich design structures, it will be more intuitive to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This research can promote the application of virtual reality technology in landscape design. Through the research, it can be found that digital and virtual reality technologies have been widely used in landscape design and landscape design teaching, which is also a development trend in the field of landscape design (Cao, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…This research can promote the application of virtual reality technology in landscape design. Through the research, it can be found that digital and virtual reality technologies have been widely used in landscape design and landscape design teaching, which is also a development trend in the field of landscape design (Cao, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…On this basis, even the economy of selling virtual spaces and tools arises, well developed in Second Life [12]. The design possibilities of a safe environment, as researchers point out, are in virtual space at the stage of offering numerous modeling tools and creating models of individual areas, zones and objects [5,6,27]. The use of Big Data and AI for urban planning is yet to be separated from the design of green environments [1,2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…and habitats for some adapted wild species are only part of the design of cities of the future [5]. These challenges require multi-factorial modeling of both technical and social processes and the active participation of society and local communities in shaping and maintaining the landscape [6,7]. Virtual spaces and worlds may be the most important modern means of such collaborative design [8].…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%